Case Report: A case of Kounis syndrome induced by iodine contrast agent during coronary angiography - Sun, Yangliu; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2024)
Kounis Syndrome (KS), a seldom-seen adverse reaction to iodine contrast agents, has an incidence that remains unclear. At present, there are no unified guidelines for managing KS either nationally or internationally. Ioversol, a new triiodinated hypotonic nonionic contrast agent, is commonly used in cardiovascular Computed Tomography (CT) and vascular imaging for diagnostic purposes. Its principal adverse reactions encompass fever, dermatological responses, convulsions, respiratory distress, hypersensitivity reactions including KS, and acute renal injury. This paper documents a case of KS induced by an iodine contrast agent during coronary angiography and, at the same time, searches for related literature and carries out a summary analysis in an attempt to provide a dependable reference for clinicians to make accurate diagnoses and treatments.